The Influence Of Nurse’s Interpersonal Communication On The Level Of BPJS Patient’s Satisfaction In Gading Medika Hospital Of Bengkulu - Putra, Yoan Mandala; Narti , Sri; Octaviani , Vethy (Universitas Dehasen Bengkulu, 2024)
This study aims to examine the influence of nurses' interpersonal communication on the level of satisfaction of BPJS patients at Gading Medika Hospital, Bengkulu. The population in this study was all BPJS patients undergoing treatment in the inpatient room at Gading Medika Hospital, Bengkulu in February 2024, totaling 849 patients. Using the Slovin formula, a sample of 90 patients was obtained. The data collection method uses a simple random sampling technique. This research uses a quantitative approach and data is obtained from research questionnaires. Data were analyzed using SPSS version 26 software. The results showed that nurses' interpersonal communication had a significant influence on the level of BPJS patient satisfaction at Gading Medika Hospital, Bengkulu. This is proven by the results of the t test, that the test results for the nurse interpersonal communication variable show a significant value of 0.013 <0.05, so the hypothesis is accepted. The conclusion of this research is that nurses' interpersonal communication influences the level of BPJS patient satisfaction at Gading Medika Hospital, Bengkulu. Nurses' interpersonal communication is good and professional, the level of patient satisfaction shows that the majority of respondents are satisfied.